Results of a parents survey on the single-use baby nappies and waste treatment - Elenkova, Dilyana; Berberova , Ralitza (Annual of Natural Sciences Department, 2022)
A recent survey results show that in 2017 in EU 0 – 2 years old children have been used approximately 33 billion single-use baby nappies which are generated about 6,7 tons of waste, or, only one baby needs 2200 single-use nappies and generates 438 kg of waste per year. Despite these single-use products contain plastic, there are no specific regulations for their waste treatment and also the price of their alternative option is higher. The choice of nappy types and waste treatment depends entirely on parents. This paper aims to investigate the Bulgarian parent attitude to single-use nappies, alternative products and separate waste collection.